2007
DOI: 10.1038/sj.ijo.0803561
|View full text |Cite
|
Sign up to set email alerts
|

Leptin predicts the development of diabetes in Mauritian men, but not women: a population–based study

Abstract: Objective: To determine if levels of the adipocyte-derived hormone, leptin, predict the development of type 2 diabetes. Methods: Population-based surveys were undertaken in the multiethnic nation of Mauritius in 1987Mauritius in , 1992Mauritius in and 1998. Questionnaires, anthropometric measurements, and a 2-h 75-g oral glucose tolerance test were included. A cohort of 2330 participants who were free of diabetes, aged 25-79 years in 1987, and who were followed-up in 1992 and 1998 was studied. Serum leptin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
90
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 43 publications
5
90
0
Order By: Relevance
“…Adiponectin is known as having anti-inflammatory, antiatherogenic and insulin-sensitizing properties 1 and it has been previously demonstrated that a low concentration of this hormone is an independent predictor of the metabolic syndrome 2 , coronary heart disease 3 and type 2 diabetes 4 . In the case of leptin, mixed results have been obtained, some studies observed that a high leptin concentration is a predictor of coronary events and type 2 diabetes independently of adiposity 5,6 while others showed that the association between leptin concentrations and these major chronic diseases is largely explained by concomitant variations in body weight or BMI 7,8 . It has been recently suggested that the leptin-to-adiponectin ratio could be a better marker of cardiometabolic alterations and insulin resistance than adiponectin or leptin alone 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Adiponectin is known as having anti-inflammatory, antiatherogenic and insulin-sensitizing properties 1 and it has been previously demonstrated that a low concentration of this hormone is an independent predictor of the metabolic syndrome 2 , coronary heart disease 3 and type 2 diabetes 4 . In the case of leptin, mixed results have been obtained, some studies observed that a high leptin concentration is a predictor of coronary events and type 2 diabetes independently of adiposity 5,6 while others showed that the association between leptin concentrations and these major chronic diseases is largely explained by concomitant variations in body weight or BMI 7,8 . It has been recently suggested that the leptin-to-adiponectin ratio could be a better marker of cardiometabolic alterations and insulin resistance than adiponectin or leptin alone 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the fullycontrolled nature of the nutritional phase permitted to document sex differences in adipocytokine responses to the MedDiet with a maximum of control over confounding variables. In addition, since previous studies have suggested that associations between these adipocytokines and cardiovascular risk factors may be sex-specific 5,6,12,13 , the inclusion of both men and premenopausal women allowed us to document for the first time sex-related differences in these associations in response to the MedDiet. On the other hand, one limitation of the present study is the absence of a control diet, which limits the conclusions on true treatment effects.…”
Section: !%" "mentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of leptin have been shown to be independently associated with diabetes in some [8][9][10][11] but not all studies [7,[12][13][14][15]18]. Of these studies, only two were UK population based studies [7,10].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence regarding the association between leptin and type 2 diabetes risk is conflicting, with some studies showing positive associations [6][7][8][9][10][11] and others showing no association [12][13][14][15]. Similarly, the association between adiponectin and type 2 diabetes risk…”
Section: Introductionmentioning
confidence: 99%